Experimental Study and Optimization in Modified Air Abrasive Jet Machining on Nickel-233 Alloy Using MCDM Techniques - Rajendra Prasad, S.; Ravindranath, Dr.K.; Devakumar, Dr.M.L.S. (Manufacturing Technology Journal, 2019)
This paper demonstrates the new multi criterion decision making (MCDM) techniques were used, i.e. the weighted aggregated sum and product assessment (WASPAS) technique. This involves the modified air abrasive jet machining (MAAJM) of Nickel 233 alloy using carbide coated nozzle in 3mm dia with three responses are considered as against the process variables of injecting pressure, standoff distance, and abrasive mesh size. The optimal combination of MAAJM process parameter for simultaneous minimization of taper angle, surface roughness and maximization of MRR are injecting pressure of 0.686MPa, standoff distance 9mm and abrasive mesh size 400μm with 3 diameter carbide coated nozzle. The optimal results attained with the WASPAS technique demonstrated to good relation with another technique multi objective optimization rational analysis (MOORA).
Keywords: MOORA; Nickel 233 alloy; Process parameters; WASPAS